Business Model Canvas : THATmug / Farisa Dania Mat Zahid - Mat Zahid, Farisa Dania (2020)
From the innovation idea of the self-stirring and non-tippable mug that goes by the name THATmug, a fine-tuned plan must be in place that directs it towards a viable future business model. A Business Model Canvas (BMC) will serve to validate its business significance. Projects of technology are often solutions or processes which solve a technical problem. The problem solution, however, is designed not only for the technological barriers but also for the barriers to the market and to industry.The company must first understand its definition, how it works, and its importance to the business in order to set up a good innovative mug business canvas. This business canvas is simply a strategic startup management template for developing a new business model.It breaks down my business model into easily understandable segments: Key Partners, Key Activities, Key Resources, Value Proposals, Customer Relationships, Channels, Customer Segment, Cost Structure, and Revenue Streams.I can recognize and act on areas that can be improved by digging into those elements of the product. It also reveals clear paths for building on my innovation strategy in the organization